2013
DOI: 10.1016/j.heares.2013.01.023
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of bone conduction skull transmission by hearing thresholds and ear-canal sound pressure

Abstract: Bone conduction sound transmission in the human skull and the occlusion effect were estimated from hearing thresholds and ear-canal sound pressure (ECSP) measured by a probe tube microphone when stimulation was at three positions on the skull (ipsilateral mastoid, contralateral mastoid, and forehead). The measurements were done with the ear-canal open as well as occluded by an ear-plug. Depending on the estimation method, transcranial transmission at frequencies below 1 kHz was between -8 and 5 dB, around 0 dB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
57
1
1

Year Published

2014
2014
2025
2025

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 61 publications
(67 citation statements)
references
References 30 publications
(60 reference statements)
7
57
1
1
Order By: Relevance
“…The variability is expected in both hearing thresholds and ECSP shifts, e.g. in Reinfeldt et al (2013), the standard deviations for these measures were in general between 4 and 12 dB. In this study, the threshold shifts show a dynamic range of 20 dB at some frequencies and almost no variability at other frequencies.…”
Section: Ipsilateral and Contralateral Response Stimulating In Positsupporting
confidence: 49%
See 1 more Smart Citation
“…The variability is expected in both hearing thresholds and ECSP shifts, e.g. in Reinfeldt et al (2013), the standard deviations for these measures were in general between 4 and 12 dB. In this study, the threshold shifts show a dynamic range of 20 dB at some frequencies and almost no variability at other frequencies.…”
Section: Ipsilateral and Contralateral Response Stimulating In Positsupporting
confidence: 49%
“…hearing device is perpendicular to the skull bone and approximately in line with the measurement direction along the ear-canal, this direction might be the most important contributor to the real hearing response using a BAHA or a BCI (Stenfelt et al, 2000(Stenfelt et al, , 2005Reinfeldt et al, 2013). It was also shown in the cadaver studies that the acceleration of the contralateral cochlea with full systems in a sound fi eld was lower with the BCI than with the BAHA.…”
mentioning
confidence: 83%
“…They reported the AC and BC sounds to be similar for frequencies up to 1.5 kHz, while above 1.5 kHz the AC tone was 10 to 20 dB greater than the BC ear canal sound at cancellation. The caveat with their study is that they occluded the ear to provide the AC sound, and thereby increased the low-frequency ear-canal sound pressure generated by BC, known as the occlusion effect (Huizing, 1960;Reinfeldt et al, 2013;Stenfelt et al, 2007). Another approach was used in Stenfelt et al (2003b) where the umbo (tip of the malleus) vibration was compared to AC and BC generated ear canal sound pressure.…”
Section: Introductionmentioning
confidence: 99%
“…The latter has been attributed to several mechanisms including the reduction of the radiating surface of the ear canal walls (Tonndorf, 1972), a gradual immobilization of the tympanic membrane (Tonndorf, 1972), the stiffer bony tissue that might radiate less energy as compared to the soft tissue (Berger and Kerivan, 1983), and a gradual stiffening of the unoccluded ear canal walls (Berger and Kerivan, 1983). Reinfeldt et al (2013) showed that the ear canal occlusion effect is influenced little by the excitation location (ipsilateral mastoid, forehead, contralateral mastoid) except at 0.125 kHz where ipsilateral mastoid stimulation causes the smallest occlusion effect and at 0.5 kHz where forehead stimulation results in the smallest occlusion effect. Last, a study by Lee (2011) suggests that the earplug type becomes important once the occlusion is deep into the ear canal.…”
Section: Introductionmentioning
confidence: 99%